![D)(x+10)^2+(y+4)^2=5^2=25](https://tex.z-dn.net/?f=D%29%28x%2B10%29%5E2%2B%28y%2B4%29%5E2%3D5%5E2%3D25)
Explanation
Step 1
We know that the general equation for a circle is
![\begin{gathered} (x-h)^2+(y-k)^2=r^2 \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2%20%5C%5C%20%20%5Cend%7Bgathered%7D)
where
(h,k) is the center of the circel
and r is the radius
then, all we need to do is replace
Let
![\begin{gathered} \text{center}\Rightarrow(h,k)\Rightarrow(-10,-4) \\ \text{radius}\Rightarrow r\Rightarrow5 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7Bcenter%7D%5CRightarrow%28h%2Ck%29%5CRightarrow%28-10%2C-4%29%20%5C%5C%20%5Ctext%7Bradius%7D%5CRightarrow%20r%5CRightarrow5%20%5Cend%7Bgathered%7D)
replace the values
![\begin{gathered} (x-h)^2+(y-k)^2=r^2 \\ (x-(-10))^2+(y-(-4))^2=5^2 \\ (x+10)^2+(y+4)^2=5^2=25 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2%20%5C%5C%20%28x-%28-10%29%29%5E2%2B%28y-%28-4%29%29%5E2%3D5%5E2%20%5C%5C%20%28x%2B10%29%5E2%2B%28y%2B4%29%5E2%3D5%5E2%3D25%20%5Cend%7Bgathered%7D)
therefore, the answer is
![D)(x+10)^2+(y+4)^2=5^2=25](https://tex.z-dn.net/?f=D%29%28x%2B10%29%5E2%2B%28y%2B4%29%5E2%3D5%5E2%3D25)
I hope this helps you
Answer:
D
Step-by-step explanation:
I think it’s the second one but I’m not 100%
Did you forget to attach an image?
In 3 metres there are 300 centimetres. Each centimetre on the scale is 300 centimeters, or a ratio of 1:300. The tree is 5 centimetres on the scale. Each centimeter on the scale is 300 centimetres, therefore 5 centimetres on the scale is 1500 centimetres. 1500 centimetres is equal to 15 metres.